Pragmatist Epistemology and Jane Addams: Fundamental Concepts for the Social Paradigm of Occupational Therapy. (1st June 2016) - Morrison, Rodolfo
Abstract: The objective of this manuscript is to contribute to the education of future occupational therapists within the current paradigm of the profession. To this purpose, some of the conceptual foundations of pragmatist epistemology and philosophical contributions of the philosopher Jane Addams are presented. Some pragmatist fundamentals such as the holistic vision of the human being, the paradox of separating "knowing from doing", and giving the usefulness of the activity and knowledge primacy in the process of human development, inspired the profession of Occupational Therapy in the United States at the beginning of the twentieth century. Today, almost 100 years after the founding of the National Society for the Promotion of Occupational Therapy, pragmatism is still relevant to the profession. Specifically, its pertinence is related to the current scenario of the profession, and its powerful development in working scopes related to socio‐community fields. This helps identify how we are on the verge of another paradigm, known as Social Paradigm of the Occupation . This new social understanding of the discipline allows us to understand the relevance of professional work in community or social contexts. Future research could address how the pragmatism contributes to the understanding of occupation as a social phenomenon within this new paradigm. Copyright © 2016 John Wiley & Sons, Ltd.